A novel K2Ti8O17 nanorod photocatalyst rich in surface OH groups for efficient hydrogen production by water splitting. (27th September 2018) - Yu, Zhuobin; Wang, Ruiyi; Jia, Jianfeng; Yuan, Yong; Waclawik, Eric R.; Zheng, Zhanfeng
Abstract: K2 Ti8 O17 nanorods have been synthesized by hydrothermal method and its photocatalytic performance of water splitting under UV irradiation was studied in detail. The photocatalytic activity has been studied in the light of the effect of metal nanoparticles decoration and interface structure. The hydrogen evolution rate of K2 Ti8 O17 sample modified by Pt cocatalyst is approximately 390.17 mmol molcatalyst −1 h −1, which is about 300 times higher than that of bare K2 Ti8 O17 photocatalyst. Remarkably, the amount of surface OH groups over K2 Ti8 O17 samples have a positive correlation with the hydrogen evolution rate, which resulted from various thermal annealing temperature. It is suggested that more hydroxyl radical generated over K2 Ti8 O17 sample result in higher holes consumption via methanol oxidation reaction, which favors the electron-hole separation and thereby exhibit better photocatalytic performance for hydrogen evolution. Graphical abstract: Highlights: K2 Ti8 O17 nanorods were synthesized by a novel hydrothermal method. The hydrothermal treatment introduces a great deal of hydroxyl groups on the photocatalyst surface. The photocatalytic performance of K2 Ti8 O17 material was evaluated for water splitting. The amount of surface OH groups over K2 Ti8 O17 samples is the key factor to the hydrogen evolution rate.